2016
DOI: 10.1021/acs.jpclett.6b00708
|View full text |Cite
|
Sign up to set email alerts
|

Proteins Take up Water Before Unfolding

Abstract: Proteins perform specific biological functions that strongly depend on their three-dimensional structure. This three-dimensional structure, i.e. the way the protein folds, is strongly determined by the interaction between the protein and the water solvent. We study the dynamics of water in aqueous solutions of several globular proteins at different degrees of urea-induced unfolding, using polarization-resolved femtosecond infrared spectroscopy. We observe that a fraction of the water molecules is strongly slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…Hence, the slowing down of the hydration water appears to scale with the number of hydrophobic CH groups contained in the caffeine/taurine molecule. This result agrees with previous studies showing that hydrophobic groups have a significantly stronger retardation effect on surrounding water molecule than hydrophilic groups [14,21,22].…”
Section: Determination Of the Slow Water Fractionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, the slowing down of the hydration water appears to scale with the number of hydrophobic CH groups contained in the caffeine/taurine molecule. This result agrees with previous studies showing that hydrophobic groups have a significantly stronger retardation effect on surrounding water molecule than hydrophilic groups [14,21,22].…”
Section: Determination Of the Slow Water Fractionsupporting
confidence: 93%
“…Both caffeine and taurine are observed to slow down the reorientational dynamics of surrounding water molecules. For other organic and biological solutes a similar slowing down of the water molecules in their hydration shells has been observed [11,17,22,23]. It is also quite generally found that in the case of dilute solution (no aggregation), the number of slow water molecules scales quite well with the size of the solute.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, the thicknesses detected by QCM-A, such as 100 and 200 nm (Figs 3 , 4 and 6 ), are much larger than the actual thickness of the denatured SOD1. As proteins are denatured their structures become looser allowing them to take up more water molecules due to the increased surface area that is exposed to water [ 41 ]. Therefore, QCM-A appears to have detected an extra aqueous layer which loosely associates with the denatured SOD1 as a layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the currently used acid concentration was 0.5 mol L −1 , the molecular weight reductions observed in the present study suggest that the temperature has a more pronounced influence than acid concentration. A possible reason for this may be that higher hydrolysis temperatures assist in protein unfolding and increase molecular mobility allowing a solvent penetration in intraparticle regions, thereby weakening inter‐ and intramolecular bonds and protein interactions . However, some larger insoluble microalgae protein‐rich particles remained in the loading cell as indicated by the dark color even after acid hydrolysis at 85 °C for 4 h (Fig.…”
Section: Resultsmentioning
confidence: 99%